GE_GERICHTE P/7180/2020 vom 15. April 2025 - GE Cour de justice (2025)
LÉSION CORPORELLE SIMPLE;MISE EN DANGER DE LA VIE D'AUTRUI(ART. 129 CP);TORT MORAL;DÉPENS | CP.40; CP.123; CP.129; CPP.135.al3; CPP.433; CPP.436